2019
DOI: 10.1038/s41419-019-2025-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tet1- and Tet2-mediated DNA demethylation promotes immunomodulation of periodontal ligament stem cells

Abstract: Periodontal ligament stem cells (PDLSCs) possess great potential for clinical treatment of immune diseases due to their extensive immunomodulatory properties. However, the underlying mechanisms that govern the immunomodulatory properties of mesenchymal stem cells (MSCs) are still not fully elucidated. Here, we show that member of the Ten-eleven translocation (Tet) family, a group of DNA demethylases, are capable of regulating PDLSC immunomodulatory functions. Tet1 and Tet2 deficiency enhance PDLSC-induced T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Recently, different biological therapies have been reported and demonstrated superior efficacy and safety 24 . It has been reported that MSCs derived from different tissues such as bone marrow MSCs 25 , MSC from periodontal ligament 26 , and MSC from adipose tissue 27 could alleviate colitis. However, some researcher raised the concerns about the fate of stem cells infused to body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, different biological therapies have been reported and demonstrated superior efficacy and safety 24 . It has been reported that MSCs derived from different tissues such as bone marrow MSCs 25 , MSC from periodontal ligament 26 , and MSC from adipose tissue 27 could alleviate colitis. However, some researcher raised the concerns about the fate of stem cells infused to body.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of exosomes, exosome protein was isolated from the culture supernatant of 4 × 10 6 cells, and 10 μg of total exosome proteins was loaded. For western analysis of cells, the 10 μg proteins were loaded for western blot as per our previously described report 26 . The relative density was measured using ImageJ 1.49v software (Wayne Rasband).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Tet1 and Tet2 led to a hypermethylated Dkk-1 promoter, which induces Wnt/β-catenin signaling and Fasligand expression. 220 In addition, MSCs have been shown to convert conventional T lymphocytes into iTreg cells. 221 Posttranslational stability of Foxp3, through ubiquitin modifications, determines immunosuppressive function of iTreg cells.…”
Section: Regulation In Immunit Ymentioning
confidence: 99%
“…Previous studies reported that the TET protein family, which includes important enzymes of DNA demethylation, is regulated by O-glycosylation, and plays an important role in maintaining the stemness of stem cells (Zhang et al, 2014;Hahn et al, 2019;Ross and Bogdanovic, 2019;Yu et al, 2019). The dynamic protein levels of TET were investigated by electrochemical techniques because of their high sensitivity, low instrumentation cost, relatively shorter analysis times, and lack of tedious extraction procedures when compared with other analytical techniques (Pandit et al, 2017).…”
Section: Dynamic Tet Analyzed In Mammalian Oogenesis and Preimplantatmentioning
confidence: 99%